2022
DOI: 10.2478/azibna-2022-0019
|View full text |Cite
|
Sign up to set email alerts
|

Development of dual-purpose cross for meat and egg production I. Growth performance and carcass composition of the crossbred chickens in comparison to the parent lines

Abstract: The aim of the study was to develop a dual-purpose cross suitable for rearing in alternative systems and to examine its growth performance and carcass composition in comparison to the parent lines. The experiment was carried out in the experimental poultry farm in the Institute of Animal Science - Kostinbrod. The cross was developed using females of a layer type line L and cocks from line BB. The latter was based on Bresse Gauloise that is also dual purpose but mainly used for meat. The chickens from the lines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…Typically, these birds are culled immediately after hatching due to poor performance. This long-standing practice has faced extensive criticism, leading the European Union to ban the culling of male chickens [4]. France and Germany are the first countries to implement this ban, starting in 2022.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Typically, these birds are culled immediately after hatching due to poor performance. This long-standing practice has faced extensive criticism, leading the European Union to ban the culling of male chickens [4]. France and Germany are the first countries to implement this ban, starting in 2022.…”
Section: Introductionmentioning
confidence: 99%
“…Stock lines that, in conjunction with layers, could meet emerging market demands. Petkov et al [4] reported the importation of French indigenous breed Bresse Gauloise birds to the Institute of Animal Science -Kostinbrod a few years ago. This import aimed to establish a new line, BB, which is currently part of the country's gene pool.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations